2023
DOI: 10.1002/ange.202219156
|View full text |Cite
|
Sign up to set email alerts
|

N‐(Morpholine‐4‐dithio)phthalimide: A Shelf‐Stable, Bilateral Platform Molecule Enabling Access to Diverse Unsymmetrical Disulfides**

Abstract: Synthetic methods for unsymmetrical disulfides are greatly needed owing to their applications in drug discovery, linker chemistry, and materials sciences. In this study, a new shelf‐stable and easy‐to‐prepare bilateral disulfurating platform molecule, N‐(morpholine‐4‐dithio)phthalimide, has been developed for the divergent synthesis of unsymmetrical disulfides. The amino and imide leaving groups of this reagent can be orthogonally transformed. Under acidic conditions, the amino moiety undergoes selective proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 119 publications
0
0
0
Order By: Relevance
“…Notably, we found that heterocycle substituents, such as N-protected pyrrolidines, N-protected piperazine, thiophene, were well-tolerated on the alkyl bromides (17)(18)(19). Additionally, substrates containing unsaturated propargyl and allyl derivatives underwent the conversionsmoothly, providing the desired products (20,21). Next, secondary alkyl bromides were tested in the reaction.…”
Section: Substrate Scopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we found that heterocycle substituents, such as N-protected pyrrolidines, N-protected piperazine, thiophene, were well-tolerated on the alkyl bromides (17)(18)(19). Additionally, substrates containing unsaturated propargyl and allyl derivatives underwent the conversionsmoothly, providing the desired products (20,21). Next, secondary alkyl bromides were tested in the reaction.…”
Section: Substrate Scopesmentioning
confidence: 99%
“…Traditional methods to prepare disul des primarily rely on the disul de exchange or the couplings of two sulfur-containing compounds. Contemporary strategies for disul de synthesis often employ disulfurating reagent (RSS-LG) to forge C-SS bonds, with persul de cations (RSS + ) or persul de anions (RSS -) serving as crucial intermediates [9][10][11][12][13][14][15][16][17][18][19][20][21] (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%